Multiple Myeloma Cell-Derived Exosomes: Implications on Tumorigenesis, Diagnosis, Prognosis and Therapeutic Strategies - Alessandro Allegra (MDPI AG, 2021)
Multiple myeloma (MM) is a hematological disease that is still not curable. The bone marrow milieu, with cellular and non-cellular elements, participate in the creation of a pro-tumoral environment enhancing growth and survival of MM plasma cells. Exosomes are vesicles oscillating in dimension between 50 nm and 100 nm in size that can be released by various cells and contribute to the pathogenesis and progression of MM. Exosomes enclose proteins, cytokines, lipids, microRNAs, long noncoding RNAs, and circular RNAs able to regulate interactions between MM plasma cells and adjacent cells. Through exosomes, mesenchymal stem cells confer chemoresistance to MM cells, while myeloma cells promote angiogenesis, influence immune response, cause bone lesions, and have an impact on the outcome of MM patients. In this review, we analyze the role played by exosomes in the progression of monoclonal gammopathies and the effects on the proliferation of neoplastic plasma cells, and discuss the possible employment of exosomes as potential targets for the treatment of MM patients.